Global Ocean patterns and environmental controls of phytoplankton size structure revealed by satellite observations - Fusheng Cai; Shengqiang Wang; Linqi Wang; Deyong Sun; Shuyan Lang; Yongjun Jia; Hailong Zhang; Fei Tian (Global and Planetary Change, 2026)

A potent human neutralizing antibody targeting the receptor-binding site in the glycoprotein gp350 of Epstein-Barr virus - Qingtai Liang; Qian-Ying Zhu; Xin-Yan Fang; Jing Wei; Yi-En Xu; Yanan Zuo; Guo-Long Bu; Chu Xie; Sisi Shan; Cong Sun; Zheng Liu; Linqi Zhang; et al. (Science China Life Sciences, 2026)

National-level evaluation of the socio-economic benefits of biomass supply through the aeroponic technology in cultivating Short Rotation Coppice willows - Linqi Sun; Xiaogui Zheng; Alan Foy; John M. Stormonth-Darling; Pranav Pankaj Sahu; Mohammed Khandaker; Zoe M. Harris; Lirong Liu (Journal of Cleaner Production, 2026)

Synthesis of polylactic acid from solar C2 chemicals in engineered Escherichia coli - Yingchen Wang; Linqi Liu; Wenhui Sun; Xupeng Cao; Wangyin Wang; Can Li (Systems Microbiology and Biomanufacturing, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Cu-mediated proximal electronic engineering in Ni/MoO2 heterostructures for industrial alkaline hydrogen evolution - Lisong Zhong; Ying Li; Lirong Zheng; Jian Sun; Zhaohui Jin; Linqi Shi; Pengcheng Zhao; Baoyu Qi; Liu Yang; Zhongwei Chen (Chemical Engineering Journal, 2025)

TACC3 facilitates chondrocyte differentiation by attenuating abnormally activated FGFR3 signaling in achondroplasia − An in vitro study - Xiang Li; Long Bao; Xiaoyan Wang; Haiying Wu; Ting Chen; Rongrong Xie; Hui Sun; Dandan Zhang; Lili Wang; Linqi Chen (Tissue and Cell, 2025)

Carbon emissions assessment of ultra-high performance concrete in construction industry: Calculation method and case study - Sheng Li; Ge Han; Boshi Du; Zhisheng Jiang; Linqi Sun (Energy and Buildings, 2025)

A straightforward strategy to modulate ROS generation of AIE photosensitizers for type-I PDT - Zhencheng Sun; Jiaxin Wang; Minghui Xiao; Kaiyu Wu; Cheng Wang; Hao Fu; Shuyi Lv; Linqi Shi; Chunlei Zhu (Chemical Engineering Journal, 2024)

Research on CBF-YOLO detection model for common soybean pests in complex environment - Linqi Zhu; Xiaoming Li; Hongmin Sun; Yingpeng Han (Computers and Electronics in Agriculture, 2024)

Morphological and hydrodynamic properties of hydrates during dissociation in sediment - Zhixue Sun; Yifan Yin; Yuqi Wu; Zhilei Sun; Linqi Zhu; Yuting Zhan; Vahid Niasar; Senyou An (Fuel, 2023)

Contribution of soundless chemical demolition and induction heating demolition to carbon emissions reduction in urban demolition industry - Linqi Sun; Zhisheng Jiang; Chonghao Xu; Dong Lu; Ruisen Li; Yang Tan; Haibing Lu (Energy and Buildings, 2023)

Assessment of the cultivated land quality in the black soil region of Northeast China based on the field scale - Hongmin Sun; Zhao Yang; Xiaoming Li; Yanhong Hang; Meng Gao; Xue Lu; Yujie Yang; Xifan Meng; Linqi Zhu (Environmental Monitoring and Assessment, 2023)

Reservoir classification and log prediction of gas hydrate occurrence in the Qiongdongnan Basin, South China Sea - Linqi Zhu; Xueqing Zhou; Jin Sun; Yanrui Liu; Jingci Wang; Shiguo Wu (Frontiers in Marine Science, 2023)
Classifying natural gas hydrate reservoirs effectively and carrying out reservoir classification modelling is crucial, but to date, research on building artificial intelligence-assisted logging curve reservoir classification models is not abundant. As exploration and development have progressed, an increasing number of fine-grained reservoirs are being discovered, and their strong heterogeneity makes correct reservoir classification even more important. Two wells used for detecting hydrates in the Qiongdongnan (QDN) Basin are used to explore the relationship between logging response parameters and reservoir quality, as well as the method of building a logging-based reservoir classification model. Through K-means clustering and Adaboost methods, the K-means method is considered to be able to correspond to the hydrate enrichment degree, while the random forest method can establish an effective reservoir classification model (the recognition accuracy is 95%). In the different categories of reservoirs, the physical properties of the reservoirs are obviously poor, and the corresponding hydrate saturation is also low, which indicates that heterogeneity has indeed affected the enrichment of hydrates in fine-grained reservoirs. This reservoir classification research method can effectively recognize reservoirs.

Variations of soil bacterial community and denitrifier abundance with depth under different land-use types - Wanxue Han; Fenghua Wang; Linqi Zhang; Huicheng Zhao; Yuchong Zheng; Ruibo Sun; Liang Meng (Journal of Soils and Sediments, 2023)